Crescimento e produtividade qualitativa de tomateiro submetido à enxertia - Pedó, Tiago (2012)
The experiment was conducted in the period between December 2010 and June 2011, at the Capão do Leão Campus of Universidade Federal of Pelotas. The study aimed to analyze the growth and physiological characteristics of the qualitative production of tomato grafted and ungrafted under a protected environment. The seedlings were produced by the method of cutting terminal and ungrafted in polystyrene trays. After the period of budding, the seedlings were transplanted to the greenhouse and evaluated for growth, assimilate partitioning, yield and fruit quality and randomized blocks. From the comparative analysis of growth, the plants grafted on the hybrid Kaguemusha® showed a higher accumulation of dry matter at the end of the cycle and net assimilation rate (Ea) for more than 2/3 of the crop cycle. The relative growth rate, net assimilation rate and Ra peaked in the early phase of the cycle, and decreasing from then until the end of the cycle regardless of treatment. Grafting resulted in higher early, dry matter content of fruits, average fruit weight, shoot/root ratio, harvest index and total phenols, however the grafted plants were less productive than those of ungrafted. It was also that of ungrafted plants had soluble solids content and total yield than the grafted, however the distribution of these classes had a higher percentage of unmarketable fruits compared plants subjected to grafting.